Between Mystery and Riddle: From Narrative Strategy to Literary Genre - Fedunina, Olga (Slavica, 2018)
In the paper a difference is made between the mysterious and the enigmatic as fundamentallydifferent narrative and genre strategies. The first is typical of the so-called novelmysteryor the novel-myth, charcterized by the concept of impossible rational comprehensionof the mystery explained by the plot. The second represents a vast field of criminal literature,where the plot is dependent on a riddle that has a pre-given answer. The differences betweenthese two types of novels are manifested at all the main levels of poetics, especially in thespecific traits of the subject-oriented organization. However, the paper shows that the generalstrategy of the mysterious is also implemented through different moods in different criminalgenres such as classic detective stories, the police novel, the “adventurous investigation”, andthe “victim-centered investigation”. Thus, we can conclude that the mystery and the riddlecan reassemble genre constructive strategies not minus then narrative.